Anatomical Study of the Lateral Supracondylar Spur of the Humerus in a Bangladeshi Population - Haque, Shah Md Atiqul; Mehataz, Tasnova; Ahmed, Muntasir; Akter, Mahfuza; Biswas, Tithi Rani; Khanam, Sultana Razia (Community Based Medical Journal, 2026)
The lateral supracondylar spur of the humerus bone is a rare anatomical variation. Usually its presence is asymptomatic, but it may cause a variety of symptoms like compression of nerves and arteries that affects the mobility of humans. This cross-sectional, descriptive study was done in the Department of Anatomy, Mymensingh Medical College, Mymensingh, Bangladesh, between July 2021 and June 2022, to observe the lateral supracondylar spur in dry humerus bone in a Bangladeshi population. A non-randomized, convenient sampling technique was adopted. We collected 100 (43 right and 57 left) fully ossified dry human humeri. In this study, only 1 spur of the humerus was found (incidence rate 1%). The spur was found in the anterolateral aspect of the right humerus, 21.24 mm above the lateral epicondyle. It was triangular and measured approximately 14.81 mm in maximum vertical diameter (base), directed upwards and medially. The maximum width of the spur was 10.13 mm, and the maximum thickness was 7.51 mm. Knowledge of such anatomic variation is essential for anatomists, anthropologists, forensic specialists and clinicians like surgeons and radiologists. CBMJ 2026 January: vol. 15 no. 01 P:46-49